2009
DOI: 10.3109/17482960802588059
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary investigation of effect of granulocyte colony stimulating factor on amyotrophic lateral sclerosis

Abstract: We investigated the safety and efficacy of the granulocyte colony stimulating factor (G-CSF) in 13 patients with amyotrophic lateral sclerosis (ALS). Five-day administration of 2 microg/kg once a day was followed by a six-month observation period. The primary and secondary endpoints were the changes of ALS functional rating scale (ALSFRS) and the compound muscle action potential (CMAP) amplitude, respectively. We found that the declines of ALSFRS and CMAP amplitude after G-CSF administration were significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 5 publications
0
19
0
1
Order By: Relevance
“…In our study, we could not detect any significant difference in the CSF between ALS patients and control subjects, nor was there any correlation with either disease progression or prognosis. Although elevated G‐CSF and GM‐CSF in the CSF were noted in several studies (Mitchell et al., 2009; Tateishi et al., 2010), their predictive and therapeutic values in ALS were also preliminarily evaluated (Su et al., 2013; Zhang et al., 2009). Differences in race or patient selection among the studies may be cause of these discrepancies.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we could not detect any significant difference in the CSF between ALS patients and control subjects, nor was there any correlation with either disease progression or prognosis. Although elevated G‐CSF and GM‐CSF in the CSF were noted in several studies (Mitchell et al., 2009; Tateishi et al., 2010), their predictive and therapeutic values in ALS were also preliminarily evaluated (Su et al., 2013; Zhang et al., 2009). Differences in race or patient selection among the studies may be cause of these discrepancies.…”
Section: Discussionmentioning
confidence: 99%
“…G-CSF has been shown to boost immune defense, attenuate inflammation, and prolong survival in ALS mice [12,19,20]. Phase I clinical trials have confirmed G-CSF-based therapy is safe for ALS treatment [42,43,44]. The G-CSF receptor CSF3R is expressed by neurons in the brain and spinal cord, where G-CSF can stimulate neural differentiation from adult neural stem cells, and it protects against apoptotic death [14,45].…”
Section: Discussionmentioning
confidence: 99%
“…The diseased animals exhibited clinical, electrophysiological, and histopathological features similar to ALS, in particular, loss of extension reflex, which is a well known motor pattern characteristic of motor neuron diseases (Kriz et al 2003;Jaworski et al 2006), and the reduction of CMAP amplitude (Liu et al 2009;Henderson et al 2009;Zhang et al 2008). Both the ultramicroscopic and the electrophysiological analysis also confirmed that 1,2 DAB neurotoxicity affects primarily the proximal segments of the motor fibers, thus resembling one of the major clinical and pathological characteristics of ALS (Williamson and Cleveland 2001;Holzbaur 2004;Cleveland and Rothstein 2001;Bruijn and Cleveland 1996).…”
Section: Discussionmentioning
confidence: 97%